NCK Associated Protein 1 Modulated by miRNA‐214 Determines Vascular Smooth Muscle Cell Migration, Proliferation, and Neointima Hyperplasia - Tayyab Adeel Afzal; Le Anh Luong; Dan Chen; Cheng Zhang; Feng Yang; Qishan Chen; Weiwei An; Edmund Wilkes; Kenta Yashiro; Pedro R. Cutillas; Li Zhang; Qingzhong Xiao (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2016)
Background MicroRNA miR‐214 has been implicated in many biological cellular functions, but the impact of miR‐214 and its target genes on vascular smooth muscle cell (VSMC) proliferation, migration, and neointima smooth muscle cell hyperplasia is unknown. Methods and Results Expression of miR‐214 was closely regulated by different pathogenic stimuli in VSMCs through a transcriptional mechanism and decreased in response to vascular injury. Overexpression of miR‐214 in serum‐starved VSMCs significantly decreased VSMC proliferation and migration, whereas knockdown of miR‐214 dramatically increased VSMC proliferation and migration. Gene and protein biochemical assays, including proteomic analyses, showed that NCK associated protein 1 (NCKAP1)—a major component of the WAVE complex that regulates lamellipodia formation and cell motility—was negatively regulated by miR‐214 in VSMCs. Luciferase assays showed that miR‐214 substantially repressed wild‐type but not the miR‐214 binding site mutated version of NCKAP1 3′ untranslated region luciferase activity in VSMCs. This result confirmed that NCKAP1 is the functional target of miR‐214 in VSMCs. NCKAP1 knockdown in VSMCs recapitulates the inhibitory effects of miR‐214 overexpression on actin polymerization, cell migration, and proliferation. Data from cotransfection experiments also revealed that inhibition of NCKAP1 is required for miR‐214–mediated lamellipodia formation, cell motility, and growth. Importantly, locally enforced expression of miR‐214 in the injured vessels significantly reduced NCKAP1 expression levels, inhibited VSMC proliferation, and prevented neointima smooth muscle cell hyperplasia after injury. Conclusions We uncovered an important role of miR‐214 and its target gene NCKAP1 in modulating VSMC functions and neointima hyperplasia. Our findings suggest that miR‐214 represents a potential therapeutic target for vascular diseases.